Effectiveness of Modified Exercises to Improve Ball Control Skills in Elementary School Futsal Extracurricular Students in Sumedang Regency - Citra Ayu Lestari; Entan Saptani; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the effectiveness of training modification using cat-mouse games in improving ball control skills in elementary school futsal extracurricular participants in Sumedang Regency. Ball control is an important basic technique in futsal, but many players still have difficulty mastering it. Therefore, a more interactive and effective training method is needed. This study used an experimental method with a pre-test and post-test design. The research sample consisted of two groups, namely the experimental group that received training using cat-mouse games and the control group that underwent conventional training. Data were collected through passing-controlling tests before and after treatment, then analyzed using statistical tests, including normality tests, homogeneity tests, paired sample t-tests, independent t-tests, and N-Gain tests. The results showed that there was a significant increase in ball control skills in the experimental group compared to the control group. The N-Gain test analysis showed that the experimental group obtained an average score of 0.8091 (high category), while the control group only obtained an average score of 0.3033 (low category). The results of this study indicate that the cat-mouse game is one of the effective training methods in improving ball control skills in futsal games. The conclusion of this study is that the cat-mouse game can be used as an alternative interesting and effective training method in improving ball control skills in beginner futsal players. The results of this study contribute to the development of sports learning strategies, especially in the context of futsal games at elementary school level.